Effect of vacancy defects on the thermal conductivity of graphene nanoribbons: a molecular dynamics study. (1st January 2012) - Wang, Xiao-Liang; Xie, Fangwei; Zhang, Liqiang; Song, Xifu; Xi, Tao; Li, Xialong; Yang, Xiuwen; Yang, Ping
The reverse non-equilibrium molecular dynamics (RNEMD) has been performed to compute the thermal conductivity of armchair graphene nanoribbons (AGNRS) affected by vacancy defects. One- and two-atom vacancy defects are observed on the thermal conductivity of AGNRS. We find that one-atom vacancy defects can decrease the thermal conductivity significantly. Two-atom vacancy defects are located along the axial direction of AGNRS, and the thermal conductivity drops with the number of atoms between two-atom vacancies defects increasing. When two-atom vacancy defects are located along the longitudinal direction of AGNRS, the reduction of the thermal conductivity of AGNRS shows a pan shape.